2018
DOI: 10.1039/c8ta06869k
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a low-defect and highly conductive 3D graphene network to enable a high sulphur content cathode for high performance Li–S/graphene batteries

Abstract: A low-defect and highly conductive 3D graphene network to enable a high sulfur content cathode for high performance Li–S batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 72 publications
4
32
0
Order By: Relevance
“…The UPS is generally hired to get the actual work function and position of the valence band. [ 25–29 ] UV–vis was employed to figure out the band gap energies of TiO 2 and Ti 3 C 2 . According to the test results and band structure theory, the electrons are found to transfer from Ti 3 C 2 to TiO 2 once the heterojunction is established and the direction of a formed internal electric field is consistent with the theoretical simulations.…”
Section: Figurementioning
confidence: 99%
“…The UPS is generally hired to get the actual work function and position of the valence band. [ 25–29 ] UV–vis was employed to figure out the band gap energies of TiO 2 and Ti 3 C 2 . According to the test results and band structure theory, the electrons are found to transfer from Ti 3 C 2 to TiO 2 once the heterojunction is established and the direction of a formed internal electric field is consistent with the theoretical simulations.…”
Section: Figurementioning
confidence: 99%
“…The X‐ray diffractometer (XRD) patterns of CA, x PI‐CA ( x = 1, 2, 3) and 2PI‐CA/S are shown in Figure . For the CA sample, it can be found that two broad peaks at 2 θ = 21.5° and 43.5° correspond to the crystal face of (002) and (101) of graphite, indicating the existence of a graphite‐like structure . Compared with the CA sample, x PI‐CA presents a peak at about 2 θ = 20.5°.…”
Section: Resultsmentioning
confidence: 95%
“…The closeness in VBM positions for SG/S and VB provides strong evidence that overall the SG/S composite was highly conductive to electrons. It is amazing that the thorough coupling between graphene and over 80 wt% of sulfur induced such remarkable change in the electronic structures, thus leading to greatly improved electric conductivity throughout the SG/S composite owing to dramatic lifts in the VBM of SG/S towards the Fermi level thanks to the formation of heterojunctions between sulfur particles and the interlocking network of graphene flakes [52] .…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated recently that vertical graphene nanoflakes (VG) with extremely low defect contents can be synthesized by chemical vapor deposition (CVD) [48] on various substrates including amorphous carbon nanofibers [49] and carbon felt [50 , 51] . While such high-quality graphene nanoflakes are ideal conductors to both ion and electrons, the lack of defect is not helpful to absorb sulfur containing species and demonstrate chemically inert [52] .…”
Section: Introductionmentioning
confidence: 99%